Student Interest in Science Learning Using Virtual Tour Media: A Quantitative Study of Fourth-Grade Students - Tri Wulandari, Mei Rina; Idris, Muhamad; Irawan, David Budi (Papanda Publisher, 2025)
A virtual tour is an audiovisual medium in the form of images or videos of a certain location/place, allowing it to be used virtually without having to visit the location in person. The purpose of this study is to determine students' interest in IPAS (Integrated Science and Social Studies) learning using virtual tour media among fourth-grade students at SD Negeri 16 Palembang. This research is motivated by the phenomenon of the lack of learning media used during the learning process, resulting in low student enthusiasm during IPAS lessons.This study is a quantitative descriptive research using a survey method. The sample consisted of 27 fourth-grade students. Data collection techniques included questionnaires, observation, and documentation, with data analyzed using descriptive statistics.The analysis results show that virtual tour media can increase students' interest in IPAS learning. Based on the student response questionnaire, the average score was 83.35%, with 25 students showing a high level of interest when using virtual tour media in IPAS learning, representing 92% of the 27 respondents. Therefore, virtual tour media can increase students' interest in IPAS learning in grade IV at SD Negeri 16 Palembang. Consequently, the use of learning media is essential in enhancing the interest of elementary school students.